Studi Kualitas Kompos Sampah Upacara Agama Hindu Menggunakan Variasi Aktivator Mikroorganisme Lokal (MOL) - Aryasih, I Gusti Ayu Made; Posmaningsih, Dewa Ayu Agustini; Suyasa, Ida Bagus Oka; Sindunatha, I Gusti Ngr Bagus (Meditory : The Journal of Medical Laboratory, 2021)
Background: Local Microorganisms (MOL) contains carbohydrates that are high enough for the needs of microorganisms so that it can be used as an alternative material for an energy source that functions for the growth of microorganism cells to increase the nutrient content, especially in organic carbon to optimize the quality of compost fermentation to be higher. Aims: to determine the best quality of Hindu religious ceremony waste compost with various MOL activators. Methods: this type of research is The Posttest Only Control Group Design. The compost studied was a mixture of 75% Hindu religious ceremonial waste, 15% cow dung, 10% bran, and MOL from rice (P1), dung (P2), tape (P3), and without MOL (K). Results: the whole compost from this study did not have a significant difference in pH, organic carbon, nitrogen, C/N, phosphorus, potassium, moisture content, and electrical conductivity values and there were variations in compost microorganisms at MOL variations (p 0.05). Conclusion: there is no difference in the quality of the best Hindu religious ceremony waste compost with various MOL activators.